New electropolymerizable metal-free, metallophthalocyanines and their electrochemical, spectroelectrochemical studies - KOCA, ATIF (ELSEVIER SCIENCE SA, 2014)
The synthesis, characterization of newly synthesized metal-free 4 and metallophthalocyanine complexes 5-7 (MPcs, M = Ni, Co, Cu) have been presented in this work. All the new phthalocyanine compounds are characterized by a combination of IR, H-1 and C-13 NMR, mass and UV-Vis spectroscopy techniques. Voltammetric and spectroelectrochemical analyses of phthalocyanines supported the proposed structure of the synthesized complexes. All complexes were oxidatively electropolymerized on the working electrode during the repetitive anodic potential scans. Formation of thin film of the complex as a result of electropolymerization, and controlling the film characters by altering the excitation signals of the voltammetry, changing the working electrode and metal center of the complexes affects the polymerization mechanisms. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Cobalt; Synthesis; Electropolymerization; Electrochemistry; Spectroelectrochemistry; CATALYTIC-ACTIVITY; BIPHASIC SYSTEM; SINGLET OXYGEN; PHTHALOCYANINE; COBALT; PD(II)-PERFLUOROALKYLPHTHALOCYANINE; OXIDATION; BEHAVIOR; COMPLEX; SERIES